Comparison of factors associated with successful transition of care in patients with HIV versus other chronic diseases - Supinya In-iw; Budsayarut Lapwech; Boonying Manaboriboon (Elsevier, 2021)
Background: Transfer of pediatric patients to adult care is an integral part of optimizing care of chronically ill patients and requires advanced infrastructure and availability of a multidisciplinary team. Thus, assessing factors associated with transition to adult care in this and the other chronic disease group will aid in the targeting intervention programs. The aim of the study was to compare factors associated with transitional readiness and health risk behaviors between adolescents with HIV infection and other chronic diseases. Methods: Participants ages 14 to 18 were recruited from chronic care clinics at Siriraj hospital between 2015 and 2016. Self-assessment questionnaires composed of health risk behaviors and a 25-item Likert Scale transition readiness questionnaire with possible scores ranging from 25 to 100 were administered. Analysis was done by SPSS 18. Results: There were 165 adolescents who participated in the study. Median age was 16 years (range, 14-18). The overall transitional readiness average score was 54.15 ± 8.4 which showed no difference between HIV group (HIVG) and other chronic illness group (non-HIVG). The subjects in the HIVG scored significantly higher in self-management skills (13.03 ± 2.1 vs.12.09 ± 2.8, p < 0.05) than their non-HIV counterparts. However, they scored lower in their perception of transition readiness than non-HIVG (13.6 ±2.1 vs. 14.85 ± 2.5, p < 0.05). Adolescents who were not HIV-infected were more likely to not want to attend school because of their illness (OR = 4.33, 95% CI = 0.97-19.24.) Conversely, HIV-infected adolescents were more likely to used social media (OR=10.2, 95% CI = 3.26-31.98), consume alcohol beverage (OR = 2.83, 95% CI =1.23-6.49), smoked cigarettes (OR = 4.17, 95% CI =1.31-13.26), and lack STD knowledge (OR = 3.63, 95% CI = 1.49-8.81) rather than non-HIV infected adolescents. Conclusion: HIV-infected adolescents perceived their self-management skills to be higher than adolescent with other chronic diseases. However, HIV-infected adolescents still possess increased health risk behaviors. To effectively formulate transitional care practice in the Thai context, the program should be focused on health risk behaviors.